Laser-induced microinjury of the corneal basal epithelium and imaging of resident macrophage responses in a live, whole-eye preparation - Gulka, Sebastian M. D.; Gowen, Brent; Litke, Anastasia M.; Delaney, Kerry R.; Chow, Robert L. (Frontiers in Immunology, 2023)
The corneal epithelium is continuously subjected to external stimuli that results in varying degrees of cellular damage. While great deal of work has been done to study the corneal epithelial wound healing, very little has been done to study this process using live-cell imaging approaches in the intact cornea. Here, we describe a live, whole eye approach using laser scanning confocal microscopy to simultaneously induce and visualize the short-term cellular responses following microdamage to the corneal basal epithelium. Live-cell imaging of corneal cell layers was enabled using the lipophilic fluorescent dyes, SGC5 or FM4-64, which, when injected into the anterior chamber of enucleated eyes, readily penetrated and labelled cell membranes. Necrotic microdamage to a defined region of approximately 30 um x 30 um was induced by continuously scanning through the central plane of the corneal basal epithelium for at least one minute using high laser power. This whole-mount live-cell imaging and microdamage approach was used to examine resident corneal stromal macrophage (RCSM) behavior. In undamaged corneas, RCSMs remained stationary, but exhibited a constant extension and retraction of short (~5 um) semicircular, pseudopodia-like processes. Within minutes of microdamage, nearby anterior MHC class II+ RCSMs became polarized and extended projections towards the damaged region. Extension of the processes plateaued after about 30 minutes and remained stable over the course of 2-3 hours of imaging. These findings demonstrate how RCSMs are constantly surveying their surroundings and that even small microinjuries to the corneal epithelium are sufficient to illicit a rapid RCSM response. This is the first description of the real-time response of RCSMs to basal epithelial cell damage and provides a simple approach for studying wound healing, in situ, in a live-cell preparation.